1992
DOI: 10.1002/art.1780351107
|View full text |Cite
|
Sign up to set email alerts
|

Defective hypothalamic response to immune and inflammatory stimuli in patients with rheumatoid arthritis

Abstract: Objective. To determine the integrity of the hypothalamic-pituitary-adrenal (HPA) axis responses to immune/inflammatory stimuli in patients with rheumatoid arthritis (RA).Methods. Diurnal secretion of cortisol and the cytokine and cortisol responses to surgery were studied in subjects with active RA, in subjects with chronic osteomyelitis (OM), and in subjects with noninflammatory arthritis, who served as controls.Results. Patients with RA had a defective HPA response, as evidenced by a diurnal cortisol rhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
163
1
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 336 publications
(177 citation statements)
references
References 32 publications
7
163
1
3
Order By: Relevance
“…37,38 While there is some evidence that the hypothalamic-pituitary-adrenal (HPA) axis may play a role in the pathogenesis of rheumatoid arthritis in certain patients, 39 MIF does not appear to colocalize in the pituitary gland with the known expression pattern of Pit-1. 36,38,40 Since the initiation of these studies, a −173*G/C single nucleotide polymorphism (SNP) in the Mif gene promoter has been reported by Donn et al 41 and was shown to be associated with systemic-onset juvenile idiopathic arthritis (systemic-onset JIA). The possession of at least one −173*C allele was seen in 36.8% of patients with systemic-onset JIA compared with 20.3% of the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 While there is some evidence that the hypothalamic-pituitary-adrenal (HPA) axis may play a role in the pathogenesis of rheumatoid arthritis in certain patients, 39 MIF does not appear to colocalize in the pituitary gland with the known expression pattern of Pit-1. 36,38,40 Since the initiation of these studies, a −173*G/C single nucleotide polymorphism (SNP) in the Mif gene promoter has been reported by Donn et al 41 and was shown to be associated with systemic-onset juvenile idiopathic arthritis (systemic-onset JIA). The possession of at least one −173*C allele was seen in 36.8% of patients with systemic-onset JIA compared with 20.3% of the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…comparing them with cases of chronic osteomyelitis (OM) and sex-and age-matched non-inflammatory disease controls (NIA). The kinetics of TN F-a, TN F-sR55 and TNF-sR75 were also studied before and after major surgery to evaluate whether excessive release of TNF-sR could account for the defective function of the hypothalamic-pituitary-adrenal axis that we have documented in RA patients [31].…”
Section: Introductionmentioning
confidence: 99%
“…This might be explained by the possibility that disease activity is greater in the PSL group than in the non-PSL In RA patients, plasma CRH levels in the non-PSL group tended to be lower than in the OA group, and those in the PSL group were significantly lower than in OA group. These results can be explained by reference to a previous report which states that CRH secretion from the hypothalamus is disturbed in patients with RA [24]. It is also possible that, in RA patients, the HPA axis is affected by chronic pain (arthralgia) stress.…”
Section: Discussionmentioning
confidence: 52%